2018
DOI: 10.1371/journal.pgen.1007161
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase IV primarily operates outside of DNA replication forks in Escherichia coli

Abstract: In Escherichia coli, damage to the chromosomal DNA induces the SOS response, setting in motion a series of different DNA repair and damage tolerance pathways. DNA polymerase IV (pol IV) is one of three specialised DNA polymerases called into action during the SOS response to help cells tolerate certain types of DNA damage. The canonical view in the field is that pol IV primarily acts at replisomes that have stalled on the damaged DNA template. However, the results of several studies indicate that pol IV also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
109
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(123 citation statements)
references
References 83 publications
(102 reference statements)
14
109
0
Order By: Relevance
“…Impaired Pol III-ssDNA interactions (e.g., when polymerase encounters a hairpin-stem duplex) influence the susceptibility of Pol III HE to Pol IVmediated polymerase exchange (Le et al, 2017). Using single-molecule time-lapse microscopy to directly visualize fluorescently labeled pol IV in live cells, Henrikus et al (2018a) recently demonstrated that over 90% of foci induced by DNA damage form outside of replisome regions, suggesting that pol IV predominantly carries out non-replisomal functions, consistent with the postreplicative TLS in gaps behind the replisome model. However, Pol IV's access to ssDNA gaps is restricted to the first 100 min after induction of the SOS response.…”
Section: Pol IVmentioning
confidence: 99%
“…Impaired Pol III-ssDNA interactions (e.g., when polymerase encounters a hairpin-stem duplex) influence the susceptibility of Pol III HE to Pol IVmediated polymerase exchange (Le et al, 2017). Using single-molecule time-lapse microscopy to directly visualize fluorescently labeled pol IV in live cells, Henrikus et al (2018a) recently demonstrated that over 90% of foci induced by DNA damage form outside of replisome regions, suggesting that pol IV predominantly carries out non-replisomal functions, consistent with the postreplicative TLS in gaps behind the replisome model. However, Pol IV's access to ssDNA gaps is restricted to the first 100 min after induction of the SOS response.…”
Section: Pol IVmentioning
confidence: 99%
“…7). In a previous study (39), following ciprofloxacin treatment, cells exhibited a similar increase in DinB-YPet concentration; an increase in intracellular DinB-YPet (pol IV) concentrations was measured from 6 ± 1 nM prior to treatment (standard error of the mean, SE) to 34 ± 3 nM (SE) 180 min after ciprofloxacin addition. Interestingly, in this present study, we showed that inclusion of DMSO led to a significant reduction in the expression level of DinB-YPet in ciprofloxacin-treated cells.…”
Section: Resultsmentioning
confidence: 52%
“…Following antibiotic addition, we recorded time-lapse movies capturing fluorescence from Escherichia coli cells expressing a functional, YPet fusion of the DinB gene from its native promoter ( SI Appendix , Fig. 1 B, C , Materials and Methods) (39, 47). We then monitored pol IV concentrations by measuring the fluorescence intensity of DinB-YPet within cells in the presence or absence of DMSO (2% v/v) and monitored DNA binding activities by counting the number of pol IV foci per cell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, earlier work has suggested that replication forks are able to skip over the lesion, leaving a gap that will be repaired later on (4). This model of "skipping" over the lesion has been recently corroborated by in vitro works showing that repriming can take place on the leading strand (5, 6), (7), and in vivo work showing that DNA Pol IV acts mostly at gaps left behind the replication fork, rather than at stalled replication forks (8). In both models, whether the replication fork stalls at the damage, or skips over the damage, ssDNA gaps are generated downstream the lesion both in the leading and lagging strand, and need to be filled (repaired) in order to achieve chromosomal replication.…”
Section: Introductionmentioning
confidence: 87%